Conflict of interest prevention as a method of fighting corruption - Berzin, P.S.; Yeszhanov, Ye.B. (Bulletin of the Karaganda University “Law Series”, 2024)
The article discusses the issues of legal regulation of conflict of interest prevention as the most effective way to prevent corruption. The main goal of the scientific article is to develop a set of effective recommendations for preventing conflicts of interest that may arise when entering the civil service and resolving conflicts of interest in the performance of the civil service as a preventive tool for preventing violations of Public Service Ethics and bribery. The methodological basis of the study is such general and individual research methods as the method of dialectics, formal-logical, comparative-legal and control method. As a result of the article, it was established that Kazakhstan's legislation contains only the initial norms for the Prevention of conflicts of interest in the Civil Service and does not form a complete mechanism for conflicts of interest in the public sector. In conclusion, based on the analysis of foreign experience, the effectiveness of the settlement of conflicts of interest in the civil service was proved and the adoption of the law “on conflicts of interest” was proposed. As a novelty of the scientific article, a critical analysis of the legislative coverage and law enforcement practice of preventing conflicts of interest in the civil service with a systematic approach was carried out.